2021
DOI: 10.1155/2021/5569346
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Meta‐Analysis on Cognitive Benefit of Exercise after Stroke

Abstract: ObjectiveThe objective of this paper is to evaluate the cognitive benefit of exercise after stroke, so as to provide more accurate and reliable guidance for targeted exercise intervention. Methods. Randomized controlled trials of the relationship between exercise and cognition after stroke were identified in Cochrane Library and PubMed. Methodological quality was assessed using the Cochrane tool of bias. SMD and 95% confidence intervals were calculated, and Chi-squared test (Q) was adopted to estimate the hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 59 publications
(47 reference statements)
1
18
0
Order By: Relevance
“…The older adults in our study who increased their physical activity levels despite experiencing health problems were observed to be less frail. Older people who remained physically active in their 80s were less likely to be hospitalized compared with those who were less physically active [40,41]. The activity and physical activity patterns of the older people in our study had four trajectories.…”
Section: Benefits Of Maintaining or Increasing Physical Activitymentioning
confidence: 66%
“…The older adults in our study who increased their physical activity levels despite experiencing health problems were observed to be less frail. Older people who remained physically active in their 80s were less likely to be hospitalized compared with those who were less physically active [40,41]. The activity and physical activity patterns of the older people in our study had four trajectories.…”
Section: Benefits Of Maintaining or Increasing Physical Activitymentioning
confidence: 66%
“…Regarding the duration of rehabilitation training programs, it is essential to understand what predicts the effectiveness of exercise, as it can guide clinicians on how to better design exercise programs for people with stroke, as programs lasting less than 8 weeks are not long enough to elicit noticeable cognitive gains [84]. A moderator-effect analysis revealed that the 12-14-week exercise interventions are associated with the most significant magnitude of cognitive gains [85]. These results reinforce the need to use relatively long programs to rehabilitate people with stroke [85][86][87][88].…”
Section: Discussionmentioning
confidence: 99%
“…Two very recent meta-analyses by Yang and Wang [84,85] also consolidate this idea of long-term exercise (exercise programs for 12 weeks) because it explains that the cycle of intervention with exercise after stroke is mainly controlled at 12 weeks since this period has good patient tolerance, as well as potentiation of long-term effects on physical and mental health, and further explains that 8 weeks of post-stroke aerobic training is more or less the ideal period to have a positive impact on cardiopulmonary and cognitive function [85].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations